Diurnal Salivary Cortisol Profiles in Patients with Cushing’s Syndrome - Braun, Leah T.; Vogel, Frederick; Zopp, Stephanie; Rubinstein, German; Schilbach, Katharina; Künzel, Heike; Beuschlein, Felix; Reincke, Martin (Experimental and Clinical Endocrinology & Diabetes, 2022)
Background Quantification of salivary cortisol is one of the highly sensitive and specific screening parameters for Cushing’s syndrome (CS). However, only late-night salivary cortisol is part of the standard screening procedure. In this study, we aimed to analyze salivary cortisol day profiles in patients with different types of CS to test whether specific patterns might be relevant for diagnosis and subtyping.Material and Methods Among 428 patients including those with confirmed Cushing’s syndrome (N=111, of those 75 with Cushing’s disease, 27 patients with adrenal CS and nine patients with ectopic CS), autonomous cortisol secretion (N=39) or exclusion of CS (control group, N=278) salivary cortisol was measured five times a day.Results At each of the five time points, salivary cortisol was significantly higher in patients with CS compared to the control group (p≤0.001). Using the entire profile instead of one single salivary cortisol at 11 p.m. improved diagnostic accuracy (85 vs. 91%) slightly. Patients with ACTH-dependent CS had higher salivary cortisol levels than patients with adrenal CS. Also, morning cortisol was significantly higher in patients with ectopic CS than in patients with Cushing’s disease (p=0.04). Nevertheless, there was a strong overlap between diurnal profiles, and the diagnostic yield for subtyping was low.Discussion The study results show that using diurnal salivary cortisol profiles for CS diagnosis results in a limited increase in diagnostic accuracy. With significant differences between Cushing subtypes, cortisol profiles are not useful in everyday clinical practice for subtyping of CS.
Keywords: hypercortisolism; Cushing’s disease; circadian rhythm; adrenocorticotropin; pituitary; adrenal